Cover Image, Volume 4, Number 2, March 2022. Issue 2 (29th March 2022) - Tao, Jianming; Yan, Zerui; Yang, Jiangshao; Li, Jiaxin; Lin, Yingbin; Huang, Zhigao
Abstract : Front cover image : Relieving the stress or strain associated with volume change is highly desirable for high‐performance SiO x anodes in terms of stable solid electrolyte interphase (SEI)‐film growth. In article number 10.1002/cey2.141, Tao et al. demonstrate that the gradient regulation of Si‐valence can eliminate the local stress and enhance the lithium‐ion transport dynamics for SiO x anode, effectively boosting the cycle life and output power for batteries, and thus strongly driving electric vehicles.